The Impact of Regional Original Revenue, Regional Transfer Funds, Capital Expenditures, and Regional Government Surplus on Economic Growth - Rattih A Ajuan; Asrudin Hormati; Sheila Kusumaningrum (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of local original income, transfer funds to regions, capital expenditure and silpa of local governments of regencies/cities in North Maluku Province in 2021-2024. The sample in this study was 40 samples taken using saturated sampling techniques. The analysis tool used was multiple linear regression analysis of panel data using Eviews 13 as a statistical test tool. The results of the study showed that: (1) local original income did not affect economic growth, (2) transfer funds to regions did not affect economic growth, (3) capital expenditures